2015
DOI: 10.1038/emi.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

The role of C5a in acute lung injury induced by highly pathogenic viral infections

Abstract: The complement system, an important part of innate immunity, plays a critical role in pathogen clearance. Unregulated complement activation is likely to play a crucial role in the pathogenesis of acute lung injury (ALI) induced by highly pathogenic virus including influenza A viruses H5N1, H7N9, and severe acute respiratory syndrome (SARS) coronavirus. In highly pathogenic virus-induced acute lung diseases, high levels of chemotactic and anaphylatoxic C5a were produced as a result of excessive complement activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
195
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(207 citation statements)
references
References 102 publications
3
195
1
8
Order By: Relevance
“…It is known that adenovirus causes cytolysis, which accounts for tissue damage, and damaged pulmonary capillaries can contribute to respiratory failure (24). Another possible explanation is the unregulated complement activation, producing C5a and resulting in activation of phagocytic cells, generation of oxidants, release of histones, and, eventually, a cytokine storm (2526). Many previous cases of respiratory failure resulting from influenza A viruses H1N1, H5N1, and H7N9, severe acute respiratory syndrome coronavirus, and Middle East respiratory syndrome coronavirus pneumonia were associated with cytokine storms (27).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that adenovirus causes cytolysis, which accounts for tissue damage, and damaged pulmonary capillaries can contribute to respiratory failure (24). Another possible explanation is the unregulated complement activation, producing C5a and resulting in activation of phagocytic cells, generation of oxidants, release of histones, and, eventually, a cytokine storm (2526). Many previous cases of respiratory failure resulting from influenza A viruses H1N1, H5N1, and H7N9, severe acute respiratory syndrome coronavirus, and Middle East respiratory syndrome coronavirus pneumonia were associated with cytokine storms (27).…”
Section: Discussionmentioning
confidence: 99%
“…[84][85][86] However, its relationship between ARDS and complement activation has not been explored even though the role of C5b-9 was suspected to contribute to its pathogenesis 86 and C5a in highly pathogenic viral infections was also implicated in acute lung injury. 87 The activation of complement system is one of the key events in defense mechanism against sepsis. Its protective function for host rapidly identifies and eliminates invading pathogen.…”
Section: Pathophysiologic Mechanisms Involved In Ards Complement Actimentioning
confidence: 99%
“…Furthermore, as discussed above, C5a plays an important role in ROS generation and formation of NETs. Similar to TRALI, ROS and NETs have also been shown to play a role in ALI [69,[77][78][79]. Notably, it was suggested that intravascular activation of PMNs by C5a may be related to the generation of ROS, resulting in the onset of ALI [78].…”
Section: Complement Involvement In Acute Lung Injury and Ardsmentioning
confidence: 96%
“…Activation of the complement system plays an important role in ALI caused by highly pathogenic viruses such as influenza virus A (H5N1 and H7N9) and severe acute respiratory syndrome [69]. It has been shown that infection of the human host with highly pathogenic viruses such as influenza A results in complement activation and formation of C5a [69,70]. In addition, BALF and serum of mice and humans infected with fatal H1N1 virus contained increased levels of C5a [71,72].…”
Section: Complement Involvement In Acute Lung Injury and Ardsmentioning
confidence: 99%
See 1 more Smart Citation